SNAI2-Induced CircMTO1 Promotes Cell Proliferation and Inhibits Apoptosis Through the miR-320b/MCL1 Axis in Human Granulosa-Like Tumor Cells - Duan, Jie; Cai, Hongning; Huang, Yanming; Shi, Liangyan (Frontiers in Genetics, 2021)
Polycystic ovary syndrome (PCOS), one of the most common types of endocrine diseases, is characterized by a high prevalence among women of reproductive-age. However, its pathogenesis and molecular mechanisms remain unclear. CircMTO1 has been reported to participate in numerous biological processes, but, its role in PCOS progression remains unknown. In the current study, we elucidated the expression and circRNA characterization of circMTO1 in human granulosa-like tumor cells. We found that circMTO1 knockdown promoted human granulosa-like tumor cell proliferation and inhibited its apoptosis rate. Next, we explored the underlying molecular mechanisms by using a series of experiments. Our results revealed the effect of the novel circMTO1/miR-320b/MCL1 axis in human granulosa-like tumor cells. Furthermore, we found that the expression of circMTO1 was induced by Snail family transcriptional repressor 2 (SNAI2) in human granulosa-like tumor cells. Our results may provide potential targets for PCOS research and a novel direction for the diagnosis and treatment of PCOS.